Soviet Union and Anschluss of 1938 - Schweitzer V. (Научно-аналитический вестник Института Европы РАН, 2018)
Neither the West, nor the USSR assessed the forced Anschluss of an independent Austrian state in March 1938 by Hitler’s Germany as a prologue to a new world war. By their actual connivance with the Anschluss, the great powers began a "new course" towards Hitler’s Germany. Its stages were the Munich agreements between Germany, Great Britain and France in autumn 1938 on the transfer of the Czech Sudeten to the Nazis, and the treaties between the USSR and Germany in August-September 1939.